Perception about Nature of Science and its Incorporation in Teaching at Secondary Leve - WaseemAhmed, RahmatUllah Bhatti (JCTE, 2023)
The present study was designed to explore the perception of science teachers about nature of Science (NOS) and its incorporation in their teaching. The participants in this study were science teachers teaching at secondary level in Islamabad Model Colleges (IMCs). The frequency of the participants is 120 science teachers, consisting of 60 males and 60 females. The instrument used in the study was the 3-point Likert scale.